Prototype Sistem Elevator Menggunakan Motor Stepper Berbasis Atmega 16 - Wicaksono, Muhammad Jaka Wimbang; Diono, Diono; Sani, Abdullah; Dzulfiqar, Mohamad Alif; Budiana, Budiana; Aryeni, Illa; Oktani, Dessy; Kamarudin, Kamarudin; Futra, Asrizal Deri; Darmoyono, Aditya Gautama; Mahdaliza, Rahmi; Hasnira, Hasnira; Maulidiah, Hana Mutialif; Gusnam, Mu'thiana (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Negeri Batam, 2023)
Elevator are one of the most important transportation these days. Elevator is a link in a tall building that has many floors. The role of the elevator which is always used by the public requires a high level of precision. In this study, researchers made a prototype elevator system using a stepper motor and obtained test results with a maximum error rate of 2% on the 10 cm elevator input using a ruler as a testing tool. The largest comparison of testing result using a ruler and using a rotary encoder is 0.2 cm or 2 mm at the 40 cm elevator input. The precision of the elevator prototype still can be improved by using half step mode when controlling the stepper motor.